Clinical Characteristics and Risk Factors for the Recurrence of Benign Paroxysmal Positional Vertigo - Zhu, Cui Ting; Zhao, Xing Qquan; Ju, Yi; Wang, Yan; Chen, Mei Mei; Cui, Yu (Frontiers in Neurology, 2019)
Benign paroxysmal positional vertigo (BPPV) manifests itself as a paroxysm of vertigo and nystagmus lasting several seconds, which is self-limiting. The clinical characteristics and risk factors for the recurrence of BPPV in different ages have not yet been investigated. Materials and Methods: A retrospective observational study was conducted in the Department of Neurology in Beijing Tiantan Hospital from July 2009 to June 2015. The study included 1,012 patients aged 18–93 years. All patients received the definitive diagnosis and canalith repositioning maneuvers treatment and finally accomplished follow-up. Demographic variables, potential recurrence risk factors, neurological examination, and laboratory indexes were assessed. Data Analyses: The t-test or chi-squared test was first performed for group comparison, then logistic regression analysis was used to investigate the risk factors of BPPV recurrence. Results: The 1-year recurrence rates of BPPV patients after reposition maneuvers were, respectively, 22.79% (aged 18–45 years), 23.92% (aged 45–60 years), 28.89% (over 60 years). The recurrence rates among the three groups have no statistically significant difference. Logistic regression analysis shows that women BPPV patients have more recurrence risks than do men. Ménière's disease (odds ratio = 6.009, 95% confidence interval: 2.489–14.507, p < 0.001), hypertension (odds ratio = 1.510, 95% confidence interval: 1.095–2.084, p = 0.012), migraine (odds ratio = 2.534, 95% confidence interval: 1.164–5.516, p = 0.019), and hyperlipemia (odds ratio = 1.419, 95% confidence interval: 1.024–1.968, p = 0.036) were risk factors for the recurrence of BPPV in patients. Conclusion: We conclude that Ménière's disease, hypertension, migraine, and hyperlipemia may be independent risk factors for the recurrence of BPPV in patients, but aging does not increase the recurrence risk.